Constraining Born-Infeld-like nonlinear electrodynamics using hydrogen's ionization energy - Akmansoy, P. Niau; Medeiros, L. G. [UNESP] (Springer, 2018)
In this work, the hydrogen's ionization energy was used to constrain the free parameter b of three Born-Infeld-like electrodynamics namely Born-Infeld itself, Logarithmic electrodynamics and Exponential electrodynamics. An analytical methodology capable of calculating the hydrogen ground state energy level correction for a generic nonlinear electrodynamics was developed. Using the experimental uncertainty in the ground state energy of the hydrogen atom, the bound b > 5.37 x 10(20) K V/m, where K = 2, 4 root 2/3 and root pi for the Born-Infeld, Logarithmic and Exponential electrodynamics respectively, was established. In the particular case of Born-Infeld electrodynamics, the constraint found for b was compared with other constraints present in the literature.